Fluid resuscitation in acute pancreatitis - Köksal, Aydın Şeref; Parlak, Erkan (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Köksal AŞ, Parlak E. Fluid resuscitation in acute pancreatitis. Turk J Gastroenterol 2017; 28: 322-3.